Analysis of Factors Influencing Sales on SHI-DA Semarang - Alvin Ferdian (Journal of Management and Business Environment (JMBE), 2021)
The purpose of this research is to know whether the use of offline (on-site) promotion, digital payment, Instagram, and Gofood/Grabfood have effect on the sales of SHI-DA Semarang. The research used a quantitative method in the form of action research. The analysis was conducted using multiple linear regression accompanying with t-test and F-test. This research was conducted at SHI-DA Semarang using sales data of December 2019 to March 2020 and respondents comprising of SHI-DA consumers for data on marketing programs. The results revealed that marketing through digital payment (e-wallet) has an effect on sales of SHI-DA Semarang, while marketing programs through offline (on-site), Instagram, and Gofood/Grabfood individually had no effect on the sales of SHI-DA Semarang. Nevertheless, the promotions simultaneously show significant influence on the sales of SHI-DA Semarang. Thus, marketing programs through Offline (on-site) promotion, Gofood/Grabfood, and Instagram must be done simultaneously in order to have an effect on the sales of SHI-DA Semarang.